Traces in the Ocean. On Melville, Wolanowski, and Willing Suspension of Disbelief - Jędrzejko, Paweł (Review of International American Studies, 2015)
The present article locates Lucjan Wolanowski’s prose in the space of reflection upon the magical dimension of writing traditionally classified as 'non-fiction' or 'literature of fact'. The magic of 'prose factography' is addressed here both in the perspective of the conditioning of its readerly reception and in the context of the writerly potential of the 'suspension of disbelief'. The argument presented in the article aims at bringing into light the mechanisms responsible for the fusion of the material reality and rhetoric into a faith-based 'magic reality'. The acknowledgment of the role of poetic imagination in the process of shaping the reader’s awareness of the world allows one to observe that the traditional concept of 'the factual' is largely based on a volitional pursuance of the mirage of objectivity and is a product of the craving for certainty. Illustrating the central phenomena of this text with examples of the everyday experience of a Polish reader of 1980s (whose 'factual' knowledge of the world largely depended on the extent of his or her reading in reportage and travel literature), as well as with reference to Herman Melville’s Typee (a novel, which gained wide recognition only after it has been sanctioned as 'non-fiction'), the author of the article seeks to demonstrate how Lucjan Wolanowski’s prose calls into existence a 'factual reality', i.e. a reality, in which one is prone to believe, which one is inclined to take for granted, and which becomes one’s frame of reference in the context of everyday choices. If truth is a function of faith, then fact and magic merge into one and thus inescapably rendering factual reality a 'magical reality'.